An acute bout of self-myofascial release in the form of foam rolling improves performance testing - Peacock, C. A.; Krein, D. D.; Silver, T. A.; Sanders, G. J.; von Carlowitz, K.-P. A. (International Journal of Exercise Science, 2014)
Recent developments in the strength and conditioning field have shown the incorporation of foam rolling self-myofascial release in adjunct with a dynamic warm-up. This is thought to improve overall training performance; however, minimal research exists supporting this theory. Therefore, determining if an acute bout of foam rolling self-myofascial release in addition to a dynamic warm-up could influence performance is of importance. In order to do so, eleven athletically trained male subjects participated in a two condition, counterbalanced, crossover within-subjects study comparing two particular warm-up routines. The two warm-up routines compared were a total-body dynamic warm-up (DYN) and a total-body dynamic warm-up in adjunct with a self-myofascial release, total-body foam rolling session (SMR). Following each warm-up condition, subjects performed tests of flexibility, power, agility, strength, and speed. Paired samples T-tests were utilized to determine if there were any significant differences in test results between conditions (DYN vs. SMR). The data indicated that SMR was effective at improving power, agility, strength, and speed when compared to DYN (P = 0.024). A warm-up routine consisting of both a dynamic warm-up and a self-myofascial release, total-body foam rolling session resulted in overall improvements in athletic performance testing.